Design of Dual Loop Control to Attenuate Vibration of Payload Carried by a UAV - Geronel, Renan S. [UNESP]; Bueno, Douglas D. [UNESP] (MDPI, 2024)
Unmanned aerial vehicles (UAVs) are currently employed to carry different types of cargoes, such as medical products. Several advantages can be related to the integration of UAVs in health care systems, including the possibility to access remote areas, low costs and high mobility and speed. However, some concerns can arise regarding the payload integrity, especially considering medical products that can be sensitive to vibration and lose their therapeutic effect. This paper presents the flight dynamics of a quadrotor and an attached payload, assuming a flexible attachment between them. Constraint vector representation is used to model the flexible attachment and guarantee a physical distance between them. A dual loop control, formed by a sliding mode control and reduced dimension observer, is developed to improve the trajectory tracking and payload undesired oscillations. The estimated disturbance (DE) is then calculated by the difference between the estimated payload and the desired trajectories. Numerical results have shown that with the use of the DE strategy, the undesired oscillations are attenuated, showing a reduction from maximum peaks of 0.2 m to 0.05 m. Regarding performance index evaluation, a reduction of approximately 84% is observed in terms of payload oscillation. In a second case, with a different payload and external disturbance intensity, the proposed strategy is also able to positively estimate the payload vibration and, consequently, attenuate the undesired oscillation, with an 85% reduction. Therefore, the dual loop control represents an efficient strategy for tracking trajectory with low undesired oscillation intensity.
Keywords: disturbance estimation; dual loop control strategy; reduced dimension observer; sliding mode control; undesired vibration; unmanned aerial vehicle